A Pediatric Case of High-Grade Secretory Carcinoma of the Maxillary Sinus With ETV6:NTRK3 Gene Fusion, Therapeutic Implications, and Review of the Literature. (January 2023) - Cardoni, Antonello; De Vito, Rita; Milano, Giuseppe Maria; De Pasquale, Maria Debora; Alaggio, Rita
Secretory carcinoma (SC) is a salivary gland tumor with a generally low grade microscopic appearance, a characteristic immunophenotype, and a recurrent translocation leading to ETV6::NTRK3 fusion gene. Rare cases are reported in children. The maxillary sinus is an unusual localization. SC have an overall favorable prognosis, but cases with high grade morphology have been described in adult population and are related to a more aggressive clinical course. We present a pediatric case of secretory carcinoma involving the maxillary sinus with high grade morphology, with a review of the literature of secretory carcinomas with high grade component.